Children with extended oligoarticular and polyarticular juvenile idiopathic arthritis have alterations in B and T follicular cell subsets in peripheral blood and a cytokine profile sustaining B cell activation - Helena Fonseca; Cláudia Marques; Raquel Campanilho-Marques; Filipa Oliveira-Ramos; Luis Graca; Sandra Sousa; Patricia Costa-Reis; Catarina Tomé; Ana F. Mourão; Ana T. Melo; Rui L. Teixeira; Ana P. Martins; et al. (RMD Open, 2023)
Objectives The main goal of this study was to characterise the frequency and phenotype of B, T follicular helper (Tfh) and T follicular regulatory (Tfr) cells in peripheral blood and the cytokine environment present in circulation in children with extended oligoarticular juvenile idiopathic arthritis (extended oligo JIA) and polyarticular JIA (poly JIA) when compared with healthy controls, children with persistent oligoarticular JIA (persistent oligo JIA) and adult JIA patients.Methods Blood samples were collected from 105 JIA patients (children and adults) and 50 age-matched healthy individuals. The frequency and phenotype of B, Tfh and Tfr cells were evaluated by flow cytometry. Serum levels of APRIL, BAFF, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-17A, IL-21, IL-22, IFN-γ, PD-1, PD-L1, sCD40L, CXCL13 and TNF were measured by multiplex bead-based immunoassay and/or ELISA in all groups included.Results The frequency of B, Tfh and Tfr cells was similar between JIA patients and controls. Children with extended oligo JIA and poly JIA, but not persistent oligo JIA, had significantly lower frequencies of plasmablasts, regulatory T cells and higher levels of Th17-like Tfh cells in circulation when compared with controls. Furthermore, APRIL, BAFF, IL-6 and IL-17A serum levels were significantly higher in paediatric extended oligo JIA and poly JIA patients when compared with controls. These immunological alterations were not found in adult JIA patients in comparison to controls.Conclusions Our results suggest a potential role and/or activation profile of B and Th17-like Tfh cells in the pathogenesis of extended oligo JIA and poly JIA, but not persistent oligo JIA.